อุปลักษณ์เชิงมโนทัศน์จากบทเพลง J-POP - พลบุญ พราวพรรณ (Journal of Humanities and Social Sciences (HUSOKKU), 2018)
Abstract This article aims to investigate the metaphors in J-POP in relation to love and to study relationship between the metaphors and the concept of Japanese society through the use of metaphors. The research data were 400 songs compiled from the Japanese songs online during 2000 - 2017. The songs were translated and their meanings were interpreted by Japanese native speakers. The metaphors were analyzed by using the cognitive linguistic view of metaphor theory as defined by Lakoff and Johnson (1980). The finding are as follows: 1. Metaphors for love show that: love is nature, love is animate, love is inanimate, love is supernatural, love is illness, love is a journey, love is education, love is competition. 2. Metaphors for lovers reveal that: lovers are nature, lovers are animate, and lovers are drama. 3. Metaphors for women indicate that: women are nature, women are animate, and women are supernatural. 4. Metaphors for men point out that: men are nature, men are animate, and men are inanimate. All metaphors are derived from the words in the source domain. These metaphors were mapped to love, lovers, men and women in terms of appearance, characteristics, values, roles, responsibilities, and behaviors which show the cognitive concept and culture in the Japanese language. Key words: Japanese, Metaphor, Conceptual metaphor, J-POP